Bahasa Inggris - Bunga Aulia Khafifa; Anton Bawono; Dwi Yulia Hariyani; Rafidah Rizky Nasution (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2026)
This study aims to examine the impact of the Human Development Index (HDI) and the Open Unemployment Rate (TPT) on poverty in West Nusa Tenggara Province from 2019 to 2024, with Zakat serving as a moderating variable. Panel data is constructed by quantitatively combining time series data and cross-sectional data from various districts or cities utilizing secondary sources. Zakat serves as a moderating variable, whereas HDI and TPT are independent variables, with the poverty level as the dependent variable. The analysis delineates the direct and moderating impacts of zakat utilizing Moderated Regression Analysis (MRA) and Eviews 12. The findings demonstrate that poverty is significantly adversely affected by the Human Development Index (HDI), suggesting that enhancing the quality of human resources can reduce poverty. Conversely, the TPT exhibits no measurable effect on poverty, likely due to the predominance of the informal sector. The moderation study indicates that zakat does not influence the relationship between TPT and poverty; instead, it can enhance the correlation between HDI and poverty alleviation. These findings underscore the importance of improving human resource quality and managing zakat efficiently to alleviate poverty.